Microstructure of a three-way anatomical network predicts individual differences in response inhibition: a tractography study - King, Andrea Victoria; Linke, Julia; Gass, Achim; Hennerici, Michael G.; Tost, Heike; Wessa, Michèle (NeuroImage, 2012)
Response inhibition is thought to depend critically on the inferior frontal gyrus, pars opercularis (IFGoper), presupplementary motor area (preSMA) and basal ganglia, including the subthalamic nucleus (STN), but the differential contribution of structural connections within this network to response inhibition remains unclear. Using diffusion tensor imaging and probabilistic fiber tractography, we investigated the relative associations between local white matter microstructure and stop-signal response inhibition in fronto-basal ganglia tracts delineated by probabilistic tractography. In a tract-of-interest approach, we identify significant associations with fractional anisotropy (FA) in fibers connecting the right STN region to both preSMA/SMA and IFGoper and in bilateral tracts connecting preSMA/SMA to IFGoper and the striatum. In addition, significant associations with radial diffusivity (RD) were found in fibers connecting the right preSMA/SMA to striatum and in bilateral tracts between IFGoper and STN region. In our whole-brain analysis, additional significant clusters were identified in the corpus callosum, optic radiation, inferior fronto-occipital tract and white matter of the precentral gyrus. To investigate the relative importance of regional white matter characteristics to response inhibition performance, we performed a step-wise multiple regression analysis that yielded FA in tracts connecting preSMA/SMA to the STN region and striatum, respectively, and RD in fibers connecting IFGoper to the STN region as best predictors of response inhibition performance (42% explained variance). These findings point to a specific contribution of white matter pathways connecting distinct basal ganglia structures with both medial frontal and ventrolateral prefrontal regions to response inhibition.
Gesehen am 28.01.2019